PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X IPS SMA NEGERI 7 BATANG HARI - Sari, Jihan Kartika; Andriani, Lili (Universitas Batanghari Jambi, 2022)
The purpose of this study was to find out how independent learning influences the learning outcomes of class X IPS students at SMA Negeri 7 Batanghari. This research includes explanative research. The population of this study were 143 students of class X IPS. The sample of this research is 36 people. The results showed that there was a significant influence between the learning independence of class X IPS in Economics learning on student learning outcomes at SMA Negeri 7 Batang Hari. SPSS version 22 calculation results. From the calculation results above the tcount value of -062 is greater than the ttable which has a value of 000, then Ha is accepted and Ho is rejected. Keywords: Independent Learning, Learning Outcomes